Sistem Informasi Produk Unggulan Desa Kecamatan Cibingbin Berbasis Web dengan Menggunakan PHP dan MYSQL - Fauziah Fauziah (JEJARING : Jurnal Teknologi dan Manajemen Informatika, 2019)
The supreme products are the ones produced by the Village people which havehigh chances to be marketed and sold and are thus advantageous for them thisthesis which is entitled “: Information System Vilage Superior Product AtDistrict Of Cibingbin Based On Website, Use PHP And MySQL” is a mediafor marketing and selling the Village’s supreme products in the District ofCibingbin. Besides that, by the the existence of a website in the District ofCibingbin, the local officials in the District and Villages of Cibingbin can makethe news related to their regions. The input process of those product are conductedby the Village and the District’s parts. The next process of product selling isconducted by the District’s part. There are three parts who have the right to accessthe website in the District of Cibingbin, namely the District, the Villages and theCustomers